TIPians' Engagement in the Environmental Sustainability Campaigns of the Philippine Center For Environmental Protection and Sustainable Development (PCEPSDI): A Case Study in Quezon City - Jesus, Dennis A. De; Austria, Windel C. (International Journal of Atharva, 2026)
Background: Environmental sustainability remains a critical global challenge, with youth engagement identified as a crucial component in addressing issues like improper waste management. In the Philippines, understanding the factors that drive or hinder student participation in environmental campaigns is essential for fostering a culture of sustainability. This study focuses on students from the Technological Institute of the Philippines (TIPians) and their involvement with the Philippine Center for Environmental Protection and Sustainable Development, Inc. (PCEPSDI).Objectives: This study aimed to determine the level of environmental awareness and engagement of TIPians in PCEPSDI's sustainability campaigns in Quezon City. It also sought to identify perceived barriers to participation and to examine the influence of motivational factors (personal values, social influence, environmental awareness, recognition/rewards, interest/enjoyment), social media, and school-based programs on their engagement.Methods: The study employed a quantitative descriptive-correlational research design. Data were collected from 100 TIP students aged 15-24 who had participated in PCEPSDI campaigns using a structured survey questionnaire. Descriptive statistics and multiple linear regression were used for data analysis.Findings: Results revealed that TIPians possess a very high level of environmental awareness (overall mean = 4.29) and demonstrate a high level of engagement (overall mean = 3.96) in the campaigns. Perceived barriers to sustained involvement were moderate, with "lack of time" being the most significant. Motivational factors were very high (overall mean = 4.22), with environmental awareness, personal values, and interest/enjoyment being the most influential. Both social media (overall mean = 4.24) and school-based programs (overall mean = 4.21) were found to have a very high influence on student engagement.Conclusion: TIPians are highly aware of environmental issues and actively participate in sustainability campaigns, driven primarily by intrinsic motivations. While barriers like time constraints exist, the strong influence of digital platforms and school-based initiatives provides effective pathways for fostering engagement. The synergy between institutional support and intrinsic values is key to sustaining youth involvement.Novelty: This study provides localized, empirical insights into the specific context of TIP students' engagement with a non-governmental organization (PCEPSDI), offering a nuanced understanding of how motivational factors, digital tools, and academic environments collectively shape youth participation in environmental sustainability efforts within an urban Philippine setting.